The biocontrol effects and mechanisms of mycoparasitic Alternaria alternata against Chinese rose powdery mildew - Tang, Yanping; Gao, Ruotian; Ma, Changle; Wang, Jin; Li, Jing (Frontiers in Microbiology, 2025)
IntroductionChinese rose powdery mildew, caused by Podosphaera pannosa, is a devastating disease which has a significant impact on plants' ornamental and economic value. Strain KMR13, which exhibited pronounced mycoparasitic activity against P. pannosa, was isolated during the initial phase of this study; however, the underlying mechanism remains to be elucidated.MethodsIn order to analyze the biological control and mycoparasitism mechanisms, the present study was carried out to sequence the whole genome of strain KMR13 using a combination of second-generation Illumina and third-generation nanopore platforms, to mine chitinase genes from the KMR13 genome, and to screen for chitinase genes related to mycoparasitism by detecting the expression of the genes at different time periods of sporulation induction.ResultsThe results revealed a genome size of 33,532,117 base pairs (bp) with a GC content of 50.97%, encoding 12,545 genes and 379 non-coding RNAs. Functional annotations using NR, GO, KOG, Pfam, and KEGG databases identified 12,355, 8,208, 1,871, 7,911, and 7,657 genes, respectively. A total of 15 GH18 family genes were mined in KMR13, and a total of 10 chitinase genes were detected to be expressed in the transcriptome under spore induction, 5 genes were consistently up-regulated for expression after induction, and 5 genes had the highest expression at 24h of induction. RT-qPCR analysis of 5 genes with high expression as well as high fold expression showed significant differential expression for all genes, with the highest expression at 24 h of induction. Up-regulated expression of KMRChis after induction is likely to play a role in disrupting the spore wall during mycoparasitic process of strain KMR13. Field trials demonstrated that KMR13 conidial suspensions significantly suppressed P. pannosa-induced powdery mildew, although the control efficacy was lower than that observed under greenhouse conditions.DiscussionThese findings collectively highlight the potential of KMR13 as a biological control agent and provide a theoretical foundation for eco-friendly management of Chinese rose powdery mildew.